Corn : chemistry and technology - Serna Saldívar, Sergio R. Othón (Woodhead Publishing, an imprint of Elsevier, 2019)
"Corn: Chemistry and Technology, Third Edition, provides a broad perspective on corn from expert agronomists, food scientists and geneticists. This encyclopedic storehouse of comprehensive information on all aspects of the world's largest crop (in metric tons) includes extensive coverage of recent development in genetic modification for the generation of new hybrids and genotypes. New chapters highlight the importance of corn as a raw material for the production of fuel bioethanol and the emerging topic of phytochemicals or nutraceutical compounds associated to different types of corns and their effect on human health, especially in the prevention of chronic diseases and cancer. Written by international experts on corn, and edited by a highly respected academics, this new edition will remain the industry standard on the topic. Key Features: Presents new chapters that deal with specialty corns, the production of first generation bioethanol, and the important relationship of corn phytochemicals or nutraceuticals with human health; Provides contributions from a new editor and a number of new contributors who bring a fresh take on this highly successful volume; Includes vastly increased content relating to recent developments in genetic modification for the generation of new hybrids and genotypes; Contains encyclopedic coverage of grain chemistry and nutritional quality of this extensively farmed product; Covers the production and handling of corn, with both food and non-food applications."--ProQuest website.
Keywords: Corn.; Corn -- Composition.; Corn products.; elektronické knihy; electronic books